Grave mercy - LaFevers, Robin (LaFevers, Robin. His fair assassin, 2012)
In the fifteenth-century kingdom of Brittany, seventeen-year-old Ismae escapes from the brutality of an arranged marriage into the sanctuary of the convent of St. Mortain, where she learns that the god of Death has blessed her with dangerous gifts--and a violent destiny.